The Neogene and Quaternary deposits of the Barcelona city through the high-speed train line - J.M. Salvany; J. Aguirre (Geologica Acta, 2020)
A total of 208 boreholes with continuous core sampling, drilled for the construction of the high-speed train line through the city of Barcelona and other nearby infrastructures, were studied. The correlation of the lithologic logs of these boreholes allows identifying five main depositional sequences bounded by sharp erosional surfaces: i) lower Miocene, of alluvial origin; ii) middle Miocene, of deltaic-lacustrine origin; iii) lower Pliocene, of beach-shelf origin; iv) Pleistocene, of alluvial origin and v) Holocene, of deltaic origin. The erosive surfaces that separate these sequences represent important erosive hiatus linked to prolonged sea level falls at regional scale, which eliminated the upper part of each one. Sedimentation took place during decreasing intensity of extensional tectonic activity that mainly affected the Miocene deposits. The Plio-Quaternary units show their original structure apparently without tectonic alterations. Some new biostratigraphic data based on foraminifer assemblages allowed making accurate estimate of the age of the deposits.